Integrated Deterministic and Probabilistic Safety Analysis of Integrated Energy Systems with bi-directional conversion. (1st December 2020) - Chi, Lixun; Su, Huai; Zio, Enrico; Zhang, Jinjun; Li, Xueyi; Zhang, Li; Fan, Lin; Zhou, Jing; Bai, Hua
Abstract: The rapid development of the technology of energy conversion is changing the global energy landscape. In this study, a reliability analysis framework for Integrated Energy Systems (IESs) is developed, based on the concept of Integrated Deterministic and Probabilistic Safety Analysis (IDPSA). A bi-directional energy conversion system model is developed to simulate the deterministic evolution of the IES. Then, the dynamic event tree (DET) analysis technique is used to describe the stochastic evolution of IES, based on the physics of IES. Given the scenarios from the DET, the probabilistic safety margin method is used to evaluate the reliability of IES. The contract pressures at delivery points are adopted as critical safety parameters for the evaluation of the safety margins. To reduce the computational burden, Order Statistics, combining the Bracketing and Coverage approaches, are used to obtain the percentiles of the probabilistic distribution of the safety parameters. An application of the developed framework is performed on an IES. The results indicate that the framework can evaluate the reliability of IES from the perspectives of dynamic failure probability and operation performance. Furthermore, the impact of P2G (power to gas) on the energy supply and operation security of the IES is analysed in detail. Highlights: A bi-directional energy conversion system model is introduced in evaluating the reliability of IES. DET is performed to evaluate the supply reliability of IES, which can combine uncertainties and physical modelling. The probabilistic safety margin is presented to assess the reliability of supply in the contract pressure of consumers.